The Grand Ethiopian Renaissance Dam, it's impact on Egyptian agriculture and the potential for alleviating water scarcity - Hamada, Youssef M. (Environment & policy ;, 2017)
This book covers the entire Nile Basin and reflects the latest findings. It provides unique and cutting-edge insights into the region's agriculture, water resources, governance, poverty, productivity, upstream-downstream linkages, innovations, future plans and their implications. Many international summits and conferences have declared that there is an urgent need to save agriculture from its demise. Most international agencies now recognize that something must be done, but what? Beyond policy changes, the restructuring of global governance and institutional reforms are called for. Commitments must be translated into concrete actions leading to a renewed interest in agriculture and a return to the basic objective of achieving food security.